Combination of natural teeth and osseointegrated implants as prosthesis abutments in a posterior cantilever bridge - Michael Josef Kridanto Kamadjaja (Dental Journal (Majalah Kedokteran Gigi), 2008)
Dental implants have been used for several decades. Patients of all ages have chosen dental implants to replace a single tooth or several teeth or to support partial or full dentures. This paper reports two cases of patients treated with dental implant as alternative to replace the missing teeth and connected with natural tooth as abutments in a fixed restoration with distal cantilever bridge. The underlining reasons that we decided to make such kind fixed prostheses are because of clinically imposible to put the implant on certain area and the patients asked for prostheses as optimum as possible, so the mastication function could return to the homeostasis condition. The benefit of these treatments are that prostheses could be made as optimum as possible with a more economic price, so the patients feel quite satisfied. The result shows that a few years after the treatments finished there is no any disadvantageous effect of connecting teeth to implants as abutments in fixed partial dentures and there is no sign of a harmful effect to the opposing teeth either.